New Approach for Characterization and Mitigation of the Swelling Phenomenon - Bouassida, Mounir; Manigniavy, Sergio Andrew; Azaiez, Dalel; Bouassida, Yosra (Frontiers in Built Environment, 2022)
This paper introduces, first, a new method of characterisation of expansive clays after oedometer test results performed on intact Tunisian clay specimens. On the presumed expansive clays specimens, oedometer tests are preceded by the free swelling test from which the swelling pressure is measured. Further, from current oedometer test results on non-expansive clays the ratio of compression index (Cc) by the swelling index (Cs) measured during the unloading phase is determined. It revealed a clear difference for the ratio Cc/Cs determined for expansive clay specimens and the one determined for non-expansive clay specimens. Second, a novel mitigation method of the swelling phenomena is validated by using oedometer tests performed on expansive clay specimens preceded the measurement of swelling pressure. Oedometer tests performed on a half thickness clay specimen overlaid by a half thickness of sand showed a significant reduction of the swelling pressure compared to that measured on a full expansive clay specimen. The mitigation solution consists in reducing the swelling effect by placing a compacted granular layer as an interface between the expansive clay and the foundation. This solution has been adopted and approved in a forthcoming lightweight building construction at the Faculty of Sciences of Tunis City.